Analisis Teoretis Terhadap Pengaruh Faktor-Faktor Ekonomi dalam Menentukan Tingkat Fertilitas Rumah Tangga di Era Modern - Ramdana Irsyad, Ferozi; Aldi Akbar, Mhd.; Marihat Batu Bara, Radja; Purba, Bonaraja (SJEE (Scientific Journals of Economic Education), 2025)
The decline in fertility rates is a global phenomenon that is now also occurring in Indonesia, particularly in urban areas. This condition raises concerns about future demographic structure and national economic potential. One of the main factors influencing household decisions regarding the number of children is the economic factor. This study aims to theoretically analyze the influence of economic factors on household fertility rates in the modern era. The research employs a library research method with a descriptive qualitative approach. Data were obtained from scientific literature, official institutional reports, and reputable journals from the last five years. The analysis technique used is thematic content analysis, referring to three main theoretical frameworks: Household Economic Theory, Demographic Transition Theory, and Contemporary Economic Theory. The findings show that economic factors such as household income, cost of living, education expenses, women's participation in the labor force, and economic uncertainty significantly affect fertility decisions. Modern households tend to delay or limit the number of children due to the substantial costs required to raise children with quality. Moreover, an individualistic lifestyle and preferences for financial stability further reinforce the trend of smaller families. In conclusion, fertility in the modern era has increasingly become a rational economic decision rather than merely a social or cultural one. This study provides an important contribution to the development of population policies that are adaptive to the economic dynamics of society and enriches academic discourse in the fields of demography and family economics.